Overexpression of SlGATA17 Promotes Drought Tolerance in Transgenic Tomato Plants by Enhancing Activation of the Phenylpropanoid Biosynthetic Pathway - Zhao, Tingting; Wu, Tairu; Pei, Tong; Wang, Ziyu; Yang, Huanhuan; Jiang, Jingbin; Zhang, He; Chen, Xiuling; Li, Jingfu; Xu, Xiangyang (Frontiers in Plant Science, 2021)
GATA transcription factors (TFs) are widely distributed in eukaryotes. Some GATA TFs have been shown to be related to photosynthesis, germination, biorhythms and other functions in plants. In our previous study, it was found that some members of this family had obvious response when tomato plants were subjected to drought stress, in which slGATA17 gene was significantly upregulated. To further verify the function of this gene under drought stress, we constructed tomato lines with this gene overexpressed in this study. Phenotypic and physiological indicators indicated that the slGATA17-overexpressing plants were more drought-tolerant than the wild-type plants. Transcriptomic sequencing results showed that the overexpression of slGATA17 gene improved the activity of phenylpropanoid biosynthesis pathway. Especially in the initial response stage, the PAL enzyme activity assay results confirmed that the initial activity of this pathway was enhanced in transgenic plants, indicating that slGATA17 gene regulates the drought resistance of tomato plants by regulating the activity of phenylpropanoid biosynthesis pathway.